A Step-by-Step Equivalent Microprediction Method for the Mechanical Properties of Composite Solid Propellants considering Dewetting Damage - Huiru Cui; Xuan Lv; Yurong Xu; Zhiwen Zhong; Zixiang Zhou; Weili Ma (International Journal of Aerospace Engineering)
Reliable prediction of the macromechanical properties of composite solid propellants in the microscale can accelerate the development of propellants with high mechanical properties. According to the characteristics of the composition ratio of a four-component hydroxyl-terminated polybutadiene (HTPB) propellant with the component ammonium perchlorate (AP), hydroxyl-terminated polybutadiene, aluminum powder (AL), and cyclotrimethylenetrinitramine (or RDX for short), an improved random delivery algorithm was developed to separately model filler particles with the different sizes. A step-by-step equivalent representative volume element (RVE) model was generated to reflect the microstructures of the propellant. The isotropy and uniformity of the RVE model were also tested using a two-point probability function. The Park-Paulino-Roesler (PPR) cohesive model was introduced to simulate the particle debonding (or dewetting) in solid propellant. The stress-strain curves of the propellant were obtained by the macroscopic test with the extension rate 200 mm/min at different temperatures. Based on these experimental data, the 8 characteristic parameters suitable for the microinterface of the propellant were obtained by using an inversion optimization method. A microscale finite element prediction model of the propellant considering dewetting damage was constructed to study the evolution process of the microdamage of the propellant. The predicted stress-strain curves of the propellant under different loading conditions were in good agreement with the test results.